The Origins and Generation of Cancer-Associated Mesenchymal Stromal Cells: An Innovative Therapeutic Target for Solid Tumors - Li, Wei; Yang, Jin; Zheng, Ping; Li, Haining; Zhao, Shaolin (Frontiers in Oncology, 2021)
Cancer-associated mesenchymal stromal cells (CA-MSCs) have been isolated from various types of tumors and are characterized by their vigorous pro-tumorigenic functions. However, very little is known about the origins and generating process of CA-MSCs, which may facilitate the identification of biomarkers for diagnosis or innovative targets for anti-cancer therapy to restrain the tumor growth, spread and chemotherapy resistance. Current evidences have indicated that both distally recruited and local resident MSCs are the primary origins of CA-MSCs. In a tissue type-dependent mode, tumor cells together with the TME components prompt the malignant transition of tumor “naïve” MSCs into CA-MSCs in a direct cell-to-cell contact, paracrine or exosome-mediated manner. In this review, we discuss the transition of phenotypes and functions of naïve MSCs into CA-MSCs influenced by tumor cells or non-tumor cells in the TME. The key areas remaining poorly understood are also highlighted and concluded herein.